Superheavy pyrite in the Upper Cretaceous mudstone of the Songliao Basin, NE China and its implication for paleolimnological environments. (March 2020) - Cao, Hansheng; He, Wentong; Chen, Fajin; Kong, Deming
Graphical abstract: Highlights: Cretaceous mudstone of the Songliao Basin contains superheavy pyrite. The δ 34 Spyrite originated from the distilled sulfate in a sulfate minimum zone (SMZ). The distribution range of the SMZ was variable in different sedimentary stages. Continental input may have led to mixing of sulfate and attenuation of the SMZ. Abstract: The widely developed dark mudstone in the Upper Cretaceous Nenjiang Formation of the Songliao Basin is a natural archive for reconstructing the palaeoenvironment. A time series sulfur isotope study on the Nenjiang Formation reveals that authigenic pyrite from the paleo-lake is enriched in 34 S relative to coeval marine sulfate in the lower Nenjiang Member I and basal Nenjiang Member II. The occurrence of 34 S-enriched pyrite must be explained to understand the paleolimnological environment and the sulfur cycling during this period, for which several explanations can be advanced. Based on a comparison of various mechanisms for superheavy pyrite formation, we consider the presence of an anaerobic sulfate minimum zone (SMZ) in the paleo-lake as the most likely scenario. In this zone, sulfate was enriched in 34 S through microbial sulfate reduction (MSR), and this heavy sulfate became the source for pore water or bottom water, from which superheavy pyrite was produced. The conceptual model for formation of the superheavy pyrite in the Nenjiang Formation indicates that the distribution range of the SMZ was variable in the different sedimentary stages of the Nenjiang Formation. These variations were likely related to successive inputs of sulfate from continental weathering, which led to partial mixing of sulfate and attenuation of the SMZ in the basal Nenjiang Member II.